2012
DOI: 10.5007/1983-4535.2012v5n4p21
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do plano de desenvolvimento institucional das universidades federais do consórcio sul-sudeste de Minas Gerais

Abstract: A ação dos gestores públicos diante do contexto do REUNI, tem o desafio de realizar uma gestão que garanta a eficácia e eficiência organizacional, pautando-se pelo instrumento de planejamento estratégico, representado pelo Plano de Desenvolvimento Institucional – PDI, criado pelo Decreto 5.773/06. Logo, o objetivo desse artigo é avaliar os limites e as possibilidades do PDI como um instrumento gerencial mediante a visão dos docentes e técnico-administrativos das Ifes do Consórcio Sul-Sudeste. Esse artigo é par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
3
0
2
Order By: Relevance
“…By conducting a comparative analysis between the institutional development plan and methodology for strategic planning, Mizael (2012) concluded that the PDI is an excellent tool for public management of Federal Institutions of Higher Education (IFES), as a mean of pursuing excellence in teaching, research and extension, as well as achieve their goals with effectiveness, efficiency and public transparency.…”
Section: -Pdi and Strategic Planningmentioning
confidence: 99%
“…By conducting a comparative analysis between the institutional development plan and methodology for strategic planning, Mizael (2012) concluded that the PDI is an excellent tool for public management of Federal Institutions of Higher Education (IFES), as a mean of pursuing excellence in teaching, research and extension, as well as achieve their goals with effectiveness, efficiency and public transparency.…”
Section: -Pdi and Strategic Planningmentioning
confidence: 99%
“…However, it should be emphasized that the HEI can decide to use or not use the suggested structure and they can alter or incorporate other dimensions, demonstrating that these alterations must take autonomous forms of assessment into account, respecting the unique nature of each HEI. According to Mizael et al (2012), while the law leaves institutions free to draft and formulate their IDPs, it also sets criteria and requirements that curtail the creative capability of HEI.…”
Section: The Brazilian Higher Education Sectormentioning
confidence: 99%
“…Studies have also been identified that show that an IDP is the result of a collective construction. Furthermore, the limits and possibilities of an IDP are understood as a managerial tool in the view of teaching and technical-administrative staff (Mizael, Pereira, Vilas Boas, & Ferreira, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A literatura tem sugerido resultados pouco satisfatórios quanto ao PDI de organizações acadêmicas. Evidências apontam o PDI como: um instrumento cumpridor de requisitos legais, burocráticos e de uso não gerencial (MIZAEL et al, 2013); um documento descritivo de imposição legal para legitimidade entre os atores, cujas missões são vagas e intangíveis (LIMA et al, 2020); um instrumento de controle e de poder de poucos grupos (ALMEIDA; GIROGI, 2013); gerador de conflitos e tensões, que provoca ausência de sintonia entre o planejado e o executado (FALQUETO et al, 2019;MEYER JUNIOR;PASCUCI;MEYER, 2018); pouco transparente (DAL MAGRO; RAUSCH, 2012); e pouco democrático (FERREIRA; COELHO, 2020;MIZAEL et al, 2012;SILVA;VIEIRA;SILVA, 2017).…”
Section: Introductionunclassified
“…MEYER, 2018); pouco democrático na composição dos participantes internos e externos à organização (FERREIRA;COELHO, 2020;MIZAEL et al, 2012; SILVA; VIEIRA; SILVA, 2017); um PÓS-NOVA GESTÃO PÚBLICA NO PLANEJAMENTO ESTRATÉGICO DA EDUCAÇÃO PROFISSIONAL BRASILEIRA José Roberto Abreu de Carvalho Junior -Marco Aurélio Marques Ferreira 176 Revista Eletrônica de Estratégia & Negócios, Florianópolis, v.14, n. 1, jan./abr. 2021. instrumento A partir dessa seleção, buscou-se o estado com o menor Índice de Desenvolvimento Humano (IDH) 1 observando o primeiro critério de seleção e observando separadamente cada região do Brasil.…”
unclassified